Tracer Study Alumni: Sinergi Pendidikan Lulusan Prodi Keuangan dan Perbankan Syariah (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
Competition in higher education is increasingly complex, and a design is needed that makes students become superior and professional generations. The objectives of this research are (1) to produce quality graduates who have high competence in both hard skills and soft skills; (2) tracking graduates of the DIII Finance and Sharia Banking study program relevant to market needs; (3) recommendations of service users/alumni. With the existence of research on Service Users to be able to provide input on the competencies needed in the current and future world of work as well as make improvements to the curriculum. Curriculum development will always be adjusted to external developments. The method used was distributing surveys and measuring using a Likert scale. The research results from searching through the learning tracing instrument show that the average GPA of 56% is between 2.50-3.50 and the remaining cum laude is 44%. Many graduates who work after completing the DIII Finance and Sharia Banking study period are accepted by approximately 5 people, amounting to 56%. The average rate of getting a job through print media advertisements is 56% with a total of 5 people. The average salary earned by alumni is Rp. 3-5 million by 67%. To certify the authenticity of alumni tracking activities with proof of IPR and publication of journal publications